Retrieving how diplomacy writes subjects, space and time: a methodological contribution - de Orellana, Pablo (European journal of international relations, 2020)
How does diplomacy describe international actors? Diplomatic practices observe, analyse, prioritise and constitute information that is ultimately committed to text. Drawing on post-structuralist approaches to identity, diplomacy and textuality, this paper argues for consideration of the unique role of diplomatic text in constituting the state and especially its representation and understanding of Self and Other. It consequently develops a methodology to empirically analyse how the text of diplomatic communication describes people, places, time, politics, and informs policy. The analytical method proposed adjusts and expands post-structuralist discourse analysis, adapting it to the intertextual study of large collections of diplomatic knowledge production documents. It firstly determines data selection in relation to diplomacy’s own theory. Secondly, it develops an approach to retrieve how any diplomatic text constitutes representations of subjects and their contexts. Thirdly, it follows the development of representations across diplomatic knowledge production, identifying when they come to influence other international actors. This approach is demonstrated in the analysis of America’s 1945–1948 diplomatic road to involvement in Vietnam, showing how diplomacy’s representation of actors were vital to US involvement, and identifying hitherto unconsidered events, descriptions and actors. These analytics contribute to and empirically substantiate understanding of how diplomacy constitutes Self and Other, informs policy and shapes world politics.